KAJIAN DALAM PSIKOLINGUISTIK; PERANGKAT PENELITIAN, STRATEGI, DAN PENGGUNAAN METODE PENELITIAN - Busro Busro (Al Hikmah: Jurnal Studi Keislaman, 2016)
In language learning, linguistic studies should be complemented with studies interdisciplinarity between psychology and linguistics, which is commonly known Psycholinguistics, which are crucial for trying to apply knowledge of psychology and linguistics at issues such as the teaching and learning of languages, the teaching of reading the beginning and read further, bilingualism and kemultibahasaan, disease-spoken as aphasia, stuttering, and others; as well as other social problems concerning language, such as language and education, language and country and nation building. Psycholinguistics as a discipline aiming for a theory of language linguistically acceptable and psychology can explain the nature of language and pemerolehannya. Studies in psycholinguistics is competency (the process of language in communication and mind), first language acquisition, performance (the behavior patterns of language), verbal associations and the problem of meaning, the language in the abnormal perception of speech and language, and language learning.